Protocol for a multicentre, prospective, cohort study to investigate patient satisfaction and quality of life after immediate breast reconstruction in Japan: the SAQLA study. Issue 2 (15th February 2021) - Saiga, Miho; Hosoya, Yuko; Utsunomiya, Hiroki; Kuramoto, Yukiko; Watanabe, Satoko; Tomita, Koichi; Aihara, Yukiko; Muto, Mayu; Hikosaka, Makoto; Kawaguchi, Takashi; Miyaji, Tempei; Yamaguchi, Takuhiro; et al.
Abstract : Introduction: The aim of breast reconstruction (BR) is to improve patients' health-related quality of life (HRQOL). Therefore, measuring patient-reported outcomes (PROs) would clarify the value and impact of BR on a patient's life and thus would provide evidence-based information to help decision-making. The Satisfaction and Quality of Life After Immediate Breast Reconstruction study aimed to investigate satisfaction and HRQOL in Japanese patients with breast cancer who undergo immediate breast reconstruction (IBR). Methods and analysis: This ongoing prospective, observational multicentre study will assess 406 patients who had unilateral breast cancer and underwent mastectomy and IBR, and were recruited from April 2018 to July 2019. All participants were recruited from seven hospitals: Okayama University Hospital, Iwate Medical University Hospital, The Cancer Institute Hospital of Japanese Foundation for Cancer Research, Showa University Hospital, University of Tsukuba Hospital, Osaka University Hospital and Yokohama City University Medical Center. The patients will be followed up for 36 months postoperatively. The primary endpoint of this study will be the time-dependent changes in BREAST-Q satisfaction with breast subscale scores for 12 months after reconstructive surgery, which will be collected via an electronic PRO system. Ethics and dissemination: This study will be performed in accordance with the Ethical Guidelines for Medical and Health Research Involving Human Subjects published by Japan's Ministry of Education, Science and Technology and the Ministry of Health, Labour and Welfare, the modified Act on the Protection of Personal Information and the Declaration of Helsinki. This study protocol was approved by the institutional ethics committee at the Okayama University Graduate School of Medicine, Dentistry, on 2 February 2018 (1801-039) and all other participating sites. The findings of this trial will be submitted to an international peer-reviewed journal. Trial registration number: UMIN000032177.